Data Warehouse dan Data Mining Pendidikan Tinggi: Studi Kasus Kategori Undur Diri di Universitas Bina Nusantara - Heripracoyo, Sulistyo (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Data warehouse and data mining is used to extract useful information and has a specific meaning and to develop a real relationship between some variables stored in the data/data warehouse. A data warehouse is appropriately designed and added a requirement to provide appropriate data and is useful in making better decisions. Hardware and software facilitate adequate access to such data, analyze and display the results interactively. Data mining software is a highly effective tool that can be used to interrogate the data contained in the data warehouse in order to find a relationship (Neary 1999). This study conducts some literature studies applies some models and case studies in a higher education institution, in terms of the benefits, functions and development. The case study conducted is objected to see the trend and prediction of the number of students who drop out (DO).